Contrasting Warlpiri and English Language Features - Bryant, Dennis Michael (International Journal of Culture and History, 2024)
If you were to think that the English language and the Australian Aboriginal Warlpiri language are poles apart in character and nature, you could be correct, at least in principle. There are differences, of course, but the intriguing question must be whether those language differences are sufficient enough to form a strong contrast between the languages. This paper proposes the thesis that a demonstration of just a small number of differences, each of which is critical in nature, would ensure that Warlpiri will be seen, not just as apart from English, but as worlds apart from English; that is, the Warlpiri language has cleaved loyally to its heritage of complexity, while English has cleaved far away from its now distant origins and could be described as simplistic when viewed against the complex richness of Warlpiri. The methodology used in this essay is to provide Warlpiri language exemplars across a small number of the diverse differences which make Warlpiri unique in its own ways, while listing a small number of differences that make English unique. This discussion should make understandable Warlpiri youth’s recent drive to creating a parallel and successful version of their language.